LITERATURE REVIEW: PREJUDICE TERHADAP K-POPERS DI INDONESIA - Munifah, Nabilah (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2024)
In Indonesia, the growth rate of kpop is very rapid, notinfrequently boy band and girl band fans often have negativeassumptions from society. Where it tends to be viewednegatively and stereotyped as a fanatic, obsessive, hysterical,crazy, and consumptive figure. Based on previous research, noone has explained the background of the phenomenon ofpeople's views on kpopers specifically. Therefore, thisresearcher aims to find out how prejudice against kpopers inIndonesian society can arise and find out how to reduce theprejudice. The research method used is the literature studymethod. Literature searches are carried out by accessingelectronic databases online from Pubmed, Google Scholar,science direct, and other reading sources. for the selection ofjournals the author tries to classify based on the last 10 years,and the suitability of the information needed. So that the totalliterature that the author uses is 8 scientific literature consistingof books and journals. Based on the results of 8 literatureobtained information about the definition of prejudice, thesource of prejudice and how to reduce prejudice. It can beconcluded that prejudice is part of the affective or emotionalcomponent that forms a negative attitude or form of Intergrouprelations. Prejudice itself is always closely related toStereotypes and also Discrimination. Then in overcoming orreducing prejudice can be done by increasing contact fromother groups, building cooperation and interdependence,shifting stereotypes on groups with an exception, providingmulticultural education.